Pemberdayaan UMKM Telur Asin melalui Pendampingan KKN untuk Higienitas Produksi dan Pengemasan Desa Selat Narmada Lombok - Ida Ayu Nursanty; I Gst Gede Narung; M Wahyullah; Surahman Hidayat; Rosyia Wardani; Lalu Takdir Jumaidi (MAN 4 Kota Pekanbaru, 2026)
This community service activity aimed to improve production hygiene and product packaging of salted egg MSMEs in Selat Village, Narmada, West Lombok. The partners initially faced several problems, including simple production processes, suboptimal hygiene practices, and less attractive packaging. The program was implemented through a participatory KKN approach consisting of observation, production mentoring, packaging training, and evaluation. The results demonstrated improvements across key performance indicators. In terms of production hygiene, partners began to consistently implement egg washing, raw material selection, and the use of cleaner production tools. In terms of efficiency, the production process became more structured and systematic compared to the initial condition. In terms of packaging, partners adopted more attractive and standardized packaging, including better product arrangement and labeling practices. Overall, these changes indicate an increase in MSME capacity in managing production and packaging processes. As a result, the products became more organized, market-ready, and competitive. This activity contributed to strengthening MSME capacity and supporting local economic development based on village potential.